Job satisfaction and organisational commitment amongst employees in the south African department of education: Issues and challenges - Ndaleni/Sibiya, Lindiwe-Memory; Fagbadebo, Omololu; Mbandlwa, Zamokuhle (Edelweiss Applied Science and Technology, 2024)
It is common in the Umlazi and Pinetown districts of the Department of Education (DoE) that employees resign before their retirement age. Available data showed that 1,310 employees of the DoE in the two districts have resigned in the past five years. This is an indication of a sharp rise in staff turnover, with its impacts on the quality of education and service delivery. This study examined how the working environment of the districts influences job satisfaction. With 249 participants, using a mixed method, the study further examined the correlation between job satisfaction and employee turnover and how intrinsic and extrinsic motivational factors influence job satisfaction at the districts. examines how the working environment of the Department’s districts influences job satisfaction. The study further examines the correlation between job satisfaction and employee turnover at the Department of Education, as well as how intrinsic and extrinsic motivational factors influence job satisfaction. The findings of the study indicate that there is a correlation between job satisfaction and organisational commitment. The findings further indicate that due to lack of job satisfaction, employees are less committed and loyal to their organisation. The study further suggests further research on strategies that can be implemented to improve employee job satisfaction and employee commitment for the benefit of the organisations.